Aportaciones de la Coordinadora a la Cooperación Española - Álvarez Rivas, David (Revista Española de Desarrollo y Cooperación, 2023)
Since its beginning in 1986, when seven spanish developmental NGOs designed a body that could coordinate and aticulate their efforts in search of wider impact, the Spanish Developmental NGO Coordinating Committee has experienced a significant growth in its number and types of NGO as well as in its scope. While it provides accurate data about its organization ´s activities (gathered in an annual report) it also presses for a more coherent Development Aid through advocacy and its role as a memeber of the Spanish Development Aid Council.